A place called home [videorecording (DVD)] - Ann-Margret, 1941-; Settle, Matthew; Tylo, Hunter (Good Times, 2005)
A widowed belle is losing her sight, but sees more clearly than ever. With the help of a father-daughter team of grifters, she takes on the greedy niece and nephew who are trying to force her out of her house.